Change in soil microbial biomass along a rural-urban gradient in Varanasi (U.P., India). Issue 1 (2nd January 2018) - Rai, Pradeep Kumar; Rai, Anuradha; Singh, Surendra
Abstract: Soil microbial biomass has been used as an early indicator of change in soil properties resulting from urbanization. We analyzed the effect of urbanization along a rural–urban gradient on soil microbial biomass and physico-chemical properties of the soil. The mean microbial biomass carbon (MBC) value were 107.4, 121.3, and 134.2 μg g −1 of soil, respectively, for urban, sub-urban and rural sections of the gradient. Whereas, the mean microbial biomass nitrogen (MBN) was 10.2, 11.5, and 12.5 μg g −1 of soil for urban, sub-urban, and rural gradient. Similarly, the mean values of microbial biomass phosphorus (MBP) were 5.1, 5.8, and 6.3 μg g −1 of soil, for urban, sub-urban, and rural gradient, respectively. ANOVA and Tukey's Honest Significant Difference (HSD) analyses showed significant difference ( P  ≤ 0.05) in microbial biomass with physico-chemical characteristics of soils. Maximal soil microbial biomass was reported for rural soils followed by sub-urban and urban soil. Disturbance in soil texture, increased in BD and decrease in soil moisture content as major factors responsible for depletion in soil microbial biomass in urban soils. . Thus, suggesting that the urbanization adversely effected soil microbial biomass by altering natural soil characteristics.